Penggunaan Sistem Informasi dalam Perhitungan Z-Score dan Penentuan Kategori Stunting pada Balita - Krisna Widatama; Putry Wahyu Setyaningsih (Komunitas Dosen Indonesia, 2023)
Information technology is an inseparable part of human work today. It is growing very rapidly along with the human need for the speed at which information is processed until it is displayed to the user. Information systems are now widely used in all sectors, ranging from: economy, agriculture, health and so on. In the health sector, many health facilities have used information systems to improve services, one of which is Posyandu. Posyandu is the front line in providing family health services at the village level. Currently, Posyandu focus is preventing malnutrition or stunting. Standardization of stunt calculation data often changes. In addition, the calculation and documentation of toddler examination data is also still done manually. This has an impact on the efficiency of the performance of staff in determining toddlers who are affected by stunting. Data integration with the Ministry of Health is also a problem when recorded manually. Therefore, it is proposed that an information system that functions to perform Z-Score calculations and classify them into stunting or non-stunting groups. The existence of this information system can also support the government to encourage data integration between local governments and the center regarding stunting data. It is hoped that this information system can help the work efficiency of health cadres to record toddlers who fall into the Stunting category. In addition, it is also possible for the government to access data stored in the system to support data integration.